Anti-inflammatory steroids from the fruits of Artocarpus heterophyllus. Issue 18 (17th September 2021) - Liu, Yun-Yao; Wang, Ting; Yang, Rong-Xiang; Tang, Hao-Xuan; Qiang, Lei; Liu, Yan-Ping
Abstract: A phytochemical study on the fruits of Artocarpus heterophyllus caused the isolation of a previously undescribed steroid, artoheterophoid (1 ), together with seven known analogues (2 − 8 ). The chemical structure of 1 was elucidated on the basis of comprehensive spectroscopic methods and the known compounds (2 − 8 ) were identified by comparing their spectroscopic data with those reported in the literatures. All known compounds (2 –8 ) were separated from A. heterophyllus for the first time. All isolated compounds (1 –8 ) were assessed for their anti-inflammatory activities in vitro by measuring the inhibitory effect against nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells. Compounds 1 –8 displayed remarkable inhibitory effects against NO production with the IC50 values in the range of 0.72 ± 0.07 to 5.93 ± 0.12 μM. Graphical Abstract: